Correlation of technical-economic indicators at cow milk: Case studies - Rodica Chetroiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The paper presents the average results for the period 2018-2020 of 54 case studies conducted in dairy farms located in different geographical regions of Romania, different landforms and of different sizes. In terms of farm size, it is between 5.0 - 568.3 dairy cows (6,002.3 - 682,261.4 SO), of the following categories: 3.7% semi-subsistence farms, 7. 4% small farms, 77.8% medium farms and 11.1% large farms. The breeds of dairy cows exploited in the farms under the case studies are Holstein, Bæal÷tatæa cu negru româneascæa, Bæal÷tatæa româneascæa, Brunæa, as well as their crossbreds with Romanian or with imported breeds. The average size of the farms taken into account was 73.44 heads, with an average production of 4,554.94 liters / head. The average value of the unit cost was 1.55 RON / l, and the average profit per liter of milk was 0.01 RON / l, with a minimum of -0.29 RON / l and a maximum of 0.73 RON / l. The average taxable income rate was 0.22%, with a minimum of -19.51% and a maximum of 27.25%. The average profitability threshold in physical units resulting from the analyzes in the case studies is 5,506.29 liters / head, and the average profitability threshold in value units is 8,024.83 RON / head. The best correlations between technical and economic indicators indicate a very good association between total expenditures and production value, between expenditures for the main production and production value, as well as a good association between average milk production and total production value.
Keywords: O12; Q12; Q13; 330; indicators; cows; milk; expenditures; correlations